Physiotherapy: Key to the kinetics of orofacial musculature - Amandeep Sodhi; Priya K Nair; Sushmini Hegde (Wolters Kluwer Medknow Publications, 2014)
Orofacial pain disorders involve a variety of postural and functional disorders of the oral and craniofacial system. These disorders are multifactorial with muscular pain being the most common manifestation. Orofacial pain can interfere with the emotional, psychological and social well-being of the patient which in turn can affect the quality of life. Physiotherapy is a primary health care profession aimed at enhancing mobility, physical independence and quality of life. The purpose of this review is to provide an insight in to the role of physiotherapy in managing orofacial pain conditions. Using the phrase 'physiotherapy in orofacial conditions' a literature search was conducted via Pubmed, Copernicus, Scopus database and Google scholar. The first reported article in Pubmed was published in 1990 and the recently reported article was in 2014. For this systematic review, seven articles from Pubmed, two from Copernicus, two from Google Scholar, and one from Scopus database were included.